2013
DOI: 10.1177/0734242x13493955
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chlorine, sulfur and phosphorus on the volatilization behavior of heavy metals during sewage sludge thermal treatment

Abstract: Chlorine, sulfur and phosphorus were selected as element donators to investigate their effect on the volatilization behavior of heavy metals in sludge sewage incineration. Principal component analysis indicated that the promotive effect on the volatilization of heavy metals was followed by chlorine, sulfur and phosphorus. This result was proved to be correct by total release of heavy metals in sewage sludge incineration using different element donators. The release of heavy metals was very chlorine dependent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…Under pH value 6.78, phosphate ion tends to precipitate from the solution. Similar observations were given recently by [25].…”
Section: Phosphate Concentrationsupporting
confidence: 91%
“…Under pH value 6.78, phosphate ion tends to precipitate from the solution. Similar observations were given recently by [25].…”
Section: Phosphate Concentrationsupporting
confidence: 91%
“…It is clear that highly volatile (Hg, Cd) and medium volatile (Pb, Zn, As) elements showed an increased distribution to fly ash with an increase of chlorine from 1% at Umeå to 2% at Söderenergi waste fuel. These results are in agreement with previously reported values (Wang et al, 1999;Chiang et al, 2007;Luan et al, 2013). The primary reason for an increased partition to fly ash could be the formation and vaporization of metal chlorides owing to high chlorine content in input waste of Söderenergi (Chiang et al, 1997).…”
Section: Feed Chlorine Effect On Partition Of Trace Elementssupporting
confidence: 95%
“…Resulting wood product is sold to district heating plants (Andersson and Tullin, 1999). Both chlorine and sulfur are critical elements in the waste fuel with respect to element speciation, partitioning to various combustion fractions and corrosion in the boilers (Sorell, 1997;Luan et al, 2013). Speciation of trace elements is believed to be influenced by the type of chlorine bond because organic chlorine (PVC, C 2 Cl 4 ) is expected to be released as HCl in gas phase and reacts more eagerly with trace elements in comparison to inorganic (NaCl, KCl) chlorine .…”
Section: Trace Element Contents In Waste Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies (Luan et al 2013;Jiao et al 2011;Zhang et al 2008) have indicated that the partitioning behavior of heavy metals during waste incineration is influenced by the composition of the gas stream, incineration temperature, concentration of metals in the waste, and concentration of chlorine (Cl), sulfur (S), H 2 O, and so on. Because both raw sludge and dewatered sludge have high moisture levels and a low heating value, adding auxiliary fuel is necessary for the independent incineration of sludge or co-combustion of the sludge with MSW and coal.…”
Section: Introductionmentioning
confidence: 99%